Analisis Psikologis Strategi Pemasaran Digital Dalam Industri Musik: Studi Kasus pada Lagu Bunga Hati – Salma Salsabil Idol 12 - Syafrida, Alyazra (Prisani Cendekia Institute, 2024)
This research aims to conduct a psychological analysis of digital marketing strategies employed in the music industry, focusing on the song